Internalization of Islamic Character Values in Islamic Religious Education Learning at SMP Al-Azhar Mandiri Palu - Tintia Alya Sani; Nasrul Nasrul (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
This study aims to describe the process of internalizing character values in Islamic Religious Education (PAI) learning at SMP Al-Azhar Mandiri Palu. Character education is a fundamental aspect of the national education system, especially in addressing moral and social challenges in the era of globalization. Through PAI learning, schools are expected not only to transfer religious knowledge but also to instill Islamic character values such as discipline, religiosity, and tolerance. This research employs a qualitative descriptive method with a phenomenological approach, in which the researcher acts as the main instrument in collecting data through observation, interviews, and documentation. The research subjects include the principal, vice principal, Islamic Education teachers, and students. The results indicate that the internalization of character values at SMP Al-Azhar Mandiri Palu is carried out through intracurricular, co-curricular, and extracurricular activities. The value of discipline is internalized through practices such as punctual attendance, performing congregational prayers, and adherence to school rules. The religious value is cultivated through activities such as Qur'an recitation, communal prayers, regular worship habits, and teachers serving as role models for students. Meanwhile, the tolerance value is reflected in social interactions among students who respect differences in opinions, ethnicity, and cultural backgrounds. These three values are not only taught theoretically but are also applied contextually and continuously in daily school life.